Keeping a Household Inventory and Protecting Valuable Records - Carol Fountain; Michael T. Olexa; Jana Caracciolo; Lauren Grant (EDIS)
A disaster strikes. Your home and possessions are destroyed. Will you be able to pick up the pieces? You will, if you do both of the following: